Gestão da Informação e Preservação Digital : uma perspectiva portuguesa de uma mudança de paradigma - Maria Manuela Gomes de Azevedo Pinto (2009)
This article presents a Portuguese perspective regarding information management and the specific field of "digital environment", based on the research and reflection carried on the traditional areas of Archives and Libraries, their practical activities and theoretical approaches, and on the different pathways followed, with a special focus on preservation function. It includes a diachronic approach to the historical and informational process developed around the mindfact and the artefact, analysing and systematizing the ways of seeing, thinking and acting in preservation and conservation along time, as well identifying the behaviours, the problems and the challenges created by the digital environment and consequent search for solutions in the scope of the designated "digital preservation", as mapped with the analysis of six hundred sixty five programs and projects related with this field and developed in eighteen countries, during the last ten years. Having as starting point a theoretical model that assumes a systemic, holistic and complex thinking and has its epistemological foundations in the scientific area of Information Science, the results analysis reinforce the proposal of a paradigm shift based on an informational and scientific approach which constitutes the fundamental theoretical basis that will support discussion of concepts and models and the process of "knowledge management".